2013
DOI: 10.1002/art.37823
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Synovial Fluid From the Osteoarthritic Knee: Comparison With Transcriptome Analyses of Joint Tissues

Abstract: Objective The pathophysiology of the most common joint disease, osteoarthritis (OA), remains poorly understood. Since synovial fluid (SF) bathes joint cartilage and synovium, we reasoned that a comparative analysis of its protein constituents in health and OA could identify pathways involved in joint damage. A proteomic analysis of knee SF from OA patients and control subjects was performed and compared to microarray expression data from cartilage and synovium. Methods Age-matched knee SF samples from contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 49 publications
5
131
1
1
Order By: Relevance
“…The deposition and activation of increased formation of osteoclasts in joints (115) complement factors in OA cartilage have been documented in several studies in OA patients as well as in animal models of OA (94,95). Tarkowski et al observed expression of decay accelerating factor (DAF) in the synovial lining cell layer in OA along with C5b-9 terminal complement complex suggesting activation of a complement-mediated response (96,97).…”
Section: Correlation Between Synovitis and Oamentioning
confidence: 99%
“…The deposition and activation of increased formation of osteoclasts in joints (115) complement factors in OA cartilage have been documented in several studies in OA patients as well as in animal models of OA (94,95). Tarkowski et al observed expression of decay accelerating factor (DAF) in the synovial lining cell layer in OA along with C5b-9 terminal complement complex suggesting activation of a complement-mediated response (96,97).…”
Section: Correlation Between Synovitis and Oamentioning
confidence: 99%
“…Proteomic studies identified differential expression of complement proteins in human OA synovial fluid compared to control, further suggesting a potential role of these proteins in catabolic processes associated with OA. 69 …”
Section: 66mentioning
confidence: 99%
“…Ritter and Gobezie further improved the sensitivity of their method by using two-dimensional gel electrophoresis and a more sensitive LC-MS/MS system. They identified 66 proteins that were differentially present in healthy and OA synovial fluid (Ritter et al, 2013). Another study modified the immunodepletion step to yield additional insights into the synovial fluid proteome ; employing nano-LC-MALDI-TOF/TOF analysis, and after excluding the abundant proteins reported in the previous study, they identified a total of 136 proteins involved in the formation and remodeling of the extracellular matrix, including fibronectin, kininogen-1, cartilage acidic protein 1, and COMP.…”
Section: Proteomic Analysis Of Synovial Fluid In Oamentioning
confidence: 99%
“…Besides discovery proteomics, targeted proteomic analysis has been applied to the study of synovial fluid. Selected Reaction Monitoring (SRM) was applied in a study to validate differential protein expression among OA and control synovial fluids (Ritter et al, 2013). Balakrishnan et al employed Multiple Reaction Monitoring (MRM), the advanced format of SRM, to validate the expression of ANPEP, osteoglycin (OGN), and dickkopf WNT signaling pathway inhibitor 3 (DKK3).…”
Section: Proteomic Analysis Of Synovial Fluid In Oamentioning
confidence: 99%